Management of powdery mildew (Erysiphe pisi) through fungicides and persistence of bitertanol in pea (Pisum sativum) - SHARMA, I D; NATH, A; GUPTA, S K; SHYAM, K R (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the winter seasons of 1996-97 and 1997-98 to study efficacy of bitertanol, hexaconazole, fenarimal and carbendazim along with dinocap and wettable sulphur for the control of powdery mildew (Erysiphe pisi DC.) infesting pea (Pisum sativum L. sensu lato). Hexaconazole (0.05%) sprays were found effective in reducing the severity of powdery mildew, followed by fenarimol and bitertabol while maximum green pod yield was obtained in bitertanol-treated plots. Persistense of bitertanol (Baycor 25 wp) was also studied at 125.0, 187.5 and 250.0 g a i/ha on pea grown for spring harvest in Solan area of Himachal Pradesh. These deposits dissipated by 81.98 to 85.62% within 10 days on leaves. The residue half-life average was 4.0 days. The bitertanol residues in grains were 0.001 to 0.002 mg/kg on day 10. on the basis of these data, a waithing period of 7 days and a maximum residue limit of 0.2 mg/kg for bitertanol on pea were noticed.